Book Leverage in Islamic Banking in Indonesia - Intan Shaferi; Julia Safitri; Arinal Rahmati (Perisai : Islamic Banking and Finance Journal, 2021)
The purpose of this study is to examine how book leverage is in Islamic banks in Indonesia. The leverage book shows how the use of debt in Islamic banking. This study will give the results of how the lag leverage, profitability with the size of the company as the control have an effect on the book leverage of Islamic banking. This study uses Islamic banking data in Indonesia with a research period of four years, namely 2016-2019. This study used secondary data from Islamic banking and analyzed using regression. The results showed that there is an influence between lag leverage, profitability, and company size on the book leverage of Islamic banking in Indonesia.